Cognitive accessibility for literacy-enabling of young students with intellectual disabilities - Cruz, Mara Monteiro da; Monteiro, Angélica Maria Reis (Education Policy Analysis Archives, 2013)
This paper provides a description of the cognitive accessibility procedures used in the design and development of a virtual learning environment - AVALER - during a constructivisttheory supported research on literacy-enabling practices for young students with intellectual disabilities. Action-research was the chosen methodology. The subjects of the study are two teachers and nine students of a specialized school who carried out activitries characterized as "literacy-enabling practices", with the assistance of communication and information technologies, over a period of ten months. The interest of the students about the proposed activities and the spontaneous attempts to read and write were observed. Students also made associations of ideas and understood texts on "AVALER", conceived from Cognitive Flexibility Theory.